REPRODUCTIVE BEHAVIOR STUDY OF THE HUMBOLDT PENGUIN (Spheniscus humboldti), PACHACAMAC ISLAND-PERU - Amaro, Lady (2024)
The behavior of the Humboldt penguin (Spheniscus humboldti Meyen, 1834) has been studied in captivity and in the wild since the 1980s following methodologies proposed by different authors. In this article, the method of recording time budgets was used through the focal animal sampling technique to analyze the behaviors of Humboldt penguins during the reproductive period of 2010 on Pachacamac Island. There was a sampling effort of 250 hours and the analysis of the behaviors took into account the variations according to the nesting places and the months of study. As a result, 46 behaviors were recorded, grouped into 9 categories: "maintenance", "sexual-social", "aggressiveness", "nest construction", "egg care", "chick care", "locomotion", "stationary or rest" and "visual". The “stationary” categories (40.5%) and those related to the nest (25.2%) were the ones that presented the highest frequency. A significant difference was found in the behavior regarding the place of settlement and nesting of the group, as well as through the months of study. In addition, behaviors related to habitat quality and reproductive success are discussed, and recommendations are provided to evaluate the behavior of S. humboldti in future studies.